2021
DOI: 10.2147/vhrm.s295868
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carotid Intima Media Thickness and Left Ventricular Mass Index in Children with Idiopathic Nephrotic Syndrome

Abstract: Background Children with nephrotic syndrome (NS) are at a greater risk of atherosclerosis due to recurrent exposures to hyperlipidemia, hypertension, and immunosuppressive medications. CIMT (carotid intima media thickness) is a reliable marker for assessment of atherosclerosis of large and medium-sized blood vessels; endothelial dysfunction and increased CIMT usually precede the development of cardiovascular diseases. Some manifestations of NS, like proteinuria and hyperlipidemia, are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…There was no statistically significant difference between mean cIMT in children wth NS as compared to the controls. However, Rahul et al and Ahmed et al reported significantly higher mean cIMT in children with NS compared to the controls [ 19 , 22 ]. In our study, there was no significant correlation found between cIMT and duration of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant difference between mean cIMT in children wth NS as compared to the controls. However, Rahul et al and Ahmed et al reported significantly higher mean cIMT in children with NS compared to the controls [ 19 , 22 ]. In our study, there was no significant correlation found between cIMT and duration of disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study that has used PWV and augmentation index to document arterial stiffness in children with NS, as per our knowledge. Alves et al did not find any significant difference in PWV in children with NS as compared to controls (4.53 ± 0.33 m/s vs 4.52 ± 0.28 m/s, p= 0.919) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a progressive disease that occurs in the intima of large and medium-sized arteries (Ahmed, Ameen et al, 2021); it is characterized by the buildup and fusion of scattered plaques in the arterial intima. Dyslipidemia is the main risk factor for atherosclerosis (Ma, Leng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no consensus on the correlation between dyslipidemia and left ventricular mass (LVM). Research in the child population has shown total triglycerides (TG) and hypertriglyceridemia are associated with left ventricular mass (LVM) 11 . Adult studies have reported a direct correlation between total cholesterol (TC) and LVM, but only in men 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Research in the child population has shown total triglycerides (TG) and hypertriglyceridemia are associated with left ventricular mass (LVM). 11 Adult studies have reported a direct correlation between total cholesterol (TC) and LVM, but only in men. 12 However, some studies have demonstrated high-density lipoprotein cholesterol (HDL-C) is negatively correlated with LVM in patients with untreated hypertension, but TC or low-density lipoprotein cholesterol (LDL-C) is not correlated with LVM.…”
mentioning
confidence: 99%